The Decline of Established Christianity in the Western World: Interpretations and Responses - Peterson, Paul Silas (Studies in World Christianity and Interreligious Relations, 2017)
Cover; Title; Copyright; Contents; List of contributors; Foreword; Acknowledgements; 1 An introduction to the essays and to the phenomenon of established Christianity in the Western World; Part I Background issues and theoretical approaches; 2 Causes of the decline: historical, empirical and theoretical perspectives; 3 Analyzing religious decline: a sociological approach; 4 Cultural considerations in the decline of Christianity; 5 Interpretations of the decline and responses to it; Part II Case studies on specific regions and groups.